2014
DOI: 10.4329/wjr.v6.i4.62
|View full text |Cite
|
Sign up to set email alerts
|

Liver volumetry: Is imaging reliable? Personal experience and review of the literature

Abstract: The amount of the future liver remnant volume is fundamental for hepato-biliary surgery, representing an important potential risk-factor for the development of post-hepatectomy liver failure. Despite this, there is no uniform consensus about the amount of hepatic parenchyma that can be safely resected, nor about the modality that should be chosen for this evaluation. The pre-operative evaluation of hepatic volume, along with a precise identification of vascular and biliar anatomy and variants, are therefore ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 66 publications
3
46
0
1
Order By: Relevance
“…D'Onofrio et al used the same semiautomated software as we did but compared it to software running on a personal computer. They found a total liver volume of 1787.31 ml, which is comparable to the results found in the present study [14]. Certainly every method has its own limitations and it is difficult to compare absolute volumes across different studies.…”
Section: Total Liver Volumesupporting
confidence: 89%
See 2 more Smart Citations
“…D'Onofrio et al used the same semiautomated software as we did but compared it to software running on a personal computer. They found a total liver volume of 1787.31 ml, which is comparable to the results found in the present study [14]. Certainly every method has its own limitations and it is difficult to compare absolute volumes across different studies.…”
Section: Total Liver Volumesupporting
confidence: 89%
“…However, D'Onofiro et al also measured resected liver parts with different sizes with the same semiautomated software as used in the present study. They found a mean volume of resected liver parts of 1021.23 ml, which is comparable to our results, although they only used the weight of the surgical specimen as the gold standard [14]. Additionally, they did not give any information about the time needed for volumetry and reproducibility.…”
Section: Resected Liver Volumesupporting
confidence: 82%
See 1 more Smart Citation
“…15,16 Therefore, OsiriX ® liver volumetry was selected as reference measurement to compare with auto-segmentation using iNtuition ® . Volumetric analysis using OsiriX ® version 5.0.2 32-bit was performed by two observers (observer 1 and 2).…”
Section: Patientsmentioning
confidence: 99%
“…Multiple automated and semi-automated liver segmentation tools have been developed and are collectively referred to as software assisted image post-processing (SAIP) tools. [13] SAIP tools are increasing in popularity and have been proven to be very accurate in predicting liver volumes. [14,15] Studies have shown that measurement of liver volume using SAIP tools correlate well with manual volumetry, [16] and with the added advantage of being a substantially faster method of volume calculation, [17] they are being touted as the new gold standard for liver volumetry.…”
Section: Introductionmentioning
confidence: 99%